Rajhmanova vizija pastoralne teologije in duhovnikovo mesto v pokoncilski pastorali - Škafar, Vinko (Edinost in dialog, 2025)
Jože Rajhman (1924–1998), a professor of pastoral theology (assistant professor 1975, associate professor 1979, after his retirement he continued lecturing until 1993/94), was the first to present at the Maribor unit of the Faculty of Theology in Ljubljana the manuscript (lithographic) Slovenian textbook Pastirna (1873) by Lovro Vogrin, who had received his doctorate in Graz. At the Second Vatican Council, Bishop Maximilijan Držečnik of Maribor proposed and succeeded in getting the Council to recommend the subject of pastoral sociology at theological faculties in the Decree on the Pastoral Ministry of Bishops. Although he did not write a textbook on pastoral theology, Jože Rajhman, through his treatises and articles on pastoral theology, pointed to the contemporary post-Conciliar vision of pastoral care and the priest's place in post-Conciliar pastoral care. In his discussions, he made skilful use of pastoral theologians and pastoral sociologists, both foreign and domestic, in the use of conciliar documents. He stresses very strongly that the Church, and consequently pastoral theology and pastoral ministry, must deal with small groups, because this is the way to create authentic Christian communion in today's globalised world, which becomes a “redemptive communion”. In this redemptive communion, the priest will be its servant, and all the members of the communion will exercise their mission in the power of the baptismal priesthood. Rajhman's discussions and articles on the vision of pastoral theology are still challenging, as many of his points still have pastoral value today because they are rooted in the theology of the Second Vatican Council and in Christian and biblical anthropology.
Keywords: Držečnik, Maksimilijan; duhovnikovo mesto v pastorali; laiki subjekti pastorale; lay pastoral subjects; male skupine; pastoral theology; pastoralna teologija; Rajhman, Jože; small groups; the priest's place in pastoral care; Vogrin, Lovro